2013
DOI: 10.1371/journal.pone.0071094
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Histiocytic Sarcomas in a Canine Model: The Predisposed Flatcoated Retriever Dog

Abstract: BackgroundThe determination of altered expression of genes in specific tumor types and their effect upon cellular processes may create insight in tumorigenesis and help to design better treatments. The Flatcoated retriever is a dog breed with an exceptionally high incidence of histiocytic sarcomas. The breed develops two distinct entities of histiocytic neoplasia, a soft tissue form and a visceral form. Gene expression studies of these tumors have value for comparable human diseases such as histiocytic/dendrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…The biological behaviour of HS and the underlying molecular mechanisms have been subject to detailed research infrequently, and an ideal treatment scheme is still lacking . Resembling the human counterpart in many aspects, the relatively higher prevalence of HS in dogs emphasizes the dog as an interesting translational animal model . Similar to human beings, canine histiocytic sarcoma may occur as a localized and a disseminated form .…”
Section: Introductionmentioning
confidence: 99%
“…The biological behaviour of HS and the underlying molecular mechanisms have been subject to detailed research infrequently, and an ideal treatment scheme is still lacking . Resembling the human counterpart in many aspects, the relatively higher prevalence of HS in dogs emphasizes the dog as an interesting translational animal model . Similar to human beings, canine histiocytic sarcoma may occur as a localized and a disseminated form .…”
Section: Introductionmentioning
confidence: 99%
“…As well as distinguishing between different types of soft tissue sarcoma, genomic profiling can assist subclassification within sarcoma types. Microarray analysis of 15 Histiocytic sarcomas in the Flatcoated retriever identified nine genes that separated tumour from normal spleen (five downregulated; four upregulated) (Boerkamp et al, 2013) but also identified further genes that were differentially expressed between the two clinical presentations of the disease: the soft tissue form affecting limb muscles and joints and the visceral form affecting internal organs with widespread dissemination (Boerkamp et al, 2014). qRT-PCR confirmed the differential expression of three genes: C6 upregulated and VLEC12A and CCL5 downregulated in the visceral compared to the soft tissue form.…”
Section: Soft Tissue Sarcomasmentioning
confidence: 99%
“…Our previous research of HS in Flatcoated retrievers has provided evidence that the expression of nine common genes is altered when comparing both STHS and VHS with normal spleen; indicating a common ground for the general development of HS [15]. As a next step we compared the two forms of HS with one another.…”
Section: Introductionmentioning
confidence: 99%